A Novel Synthesis of Pyrazolyl Chromone Derivatives - Shanker, M.S.S.; Reddy, R.B.; Chandra Mouli, G.V.P.; Reddy, Y.D. (Asian Journal of Chemistry, 2010)
A new approach to synthesize pyrazolyl chromones (II and IV) by cyclisation of chalcones with hydrazine hydrate is reported. The behaviour of different chromones with hydrazine hydrate under different conditions is also studied. The biological activity of few selected compounds is evaluated.